Burgen & Schlösser im Harz - Griep, Hans-Günther, 1923-2016; Schadach, Volker, 1942-; Telle-Grandell, Jürgen (Goslar : Studio Schadach, 2004)
The imperial Palace at Goslar - The Harzburg und Bündheim Castle - Vienenburg - The Moates Castle Wiedelah - Stapelburg - Liebenburg Castle - Homburg - Westerburg - Ilsenburg - Werningerode Castle - Heimburg - Derenburg - Castle regenstein - Blankenburg - Qiedlinburg - Ballenstedt Castle - The Roseburg Folly - Castle Falkenstein - Castle Amstein - The Kyfhâuser - Castle Hohnstein - Sondershausen Caslte - Castle Schzrsfels - Herzberg Castle - Staufenburg - Seesen - Gandersheim - Castle Stiege - Castle Harzgerode - Stolberg Castle
U.a.: Stapelburg, Wetserburg, Ilsenburg, Schloß Wernigerode, heimburg, Derenburg, Burg Regenstein, Blankenburg, Quedlinburg, Schloß Ballenstedt, Roseburg, Burg Falkenstein, Burg Arnstein
Text dt. und engl.